That's what I thought, but I am having trouble showing that these are the only solutions. I showed that the first equation implies that \(x=a+\frac{1}{a}, y=b+\frac{1}{b}, z=c+\frac{1}{c}\) with \(abc=1\) (you can input these definitions to verify it works). Then I put those into the second equation but I got stuck.

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestI am getting \(x=y=z=2\).

Log in to reply

That's what I thought, but I am having trouble showing that these are the only solutions. I showed that the first equation implies that \(x=a+\frac{1}{a}, y=b+\frac{1}{b}, z=c+\frac{1}{c}\) with \(abc=1\) (you can input these definitions to verify it works). Then I put those into the second equation but I got stuck.

Log in to reply

Well , I didn't use the 1st equation at all. See my method:

\[xy+yz+xz=2(x+y+z) \\ \Rightarrow xy-2x+yz-2y+xz-2z=0 \\ \Rightarrow x(y-2)+y(z-2)+z(x-2) = 0\]

For the above expression to be \(0\) , we have two possible cases : \(x=y=z=0 \ or \ x=y=z=2\) of which the case of \(x=y=z=2\) is valid.

Log in to reply

Log in to reply

Log in to reply

Log in to reply